Grouper Fish Fisheries in Bays of Kwandang, Gorontalo Province are reviewed from Economic Social Aspects - Achmad, Dewi Shinta; Ali, Syamsu Alam; Sudirman, Sudirman; Indar, Yusran Nur (International Journal of Environment, Agriculture and Biotechnology, 2019)
Socio-economic information is needed in the formulation of responsible grouper management. This study aims to determine the socio-economic conditions of grouper fishermen in Bays of Kwandang. This research was conducted from January to July 2018. Primary data was collected through surveys and direct interviews with fishermen and fishermen figures.. The Collecting data using questionnaire assistance on 35 people respondents. Grouper fishermen in Bays of Kwandang were still in the category of traditional fishermen. The income of fishermen is below of Rp. 200,000/trip with the catch per trip less than 25 kg. To improve welfare, fishermen need subsidies from the local government. The subsidies are in form of fishing fleets and capital to develop business diversification in the fisheries sector.